DNA recombinant molecules carrying different allels of human preproinsulin gene as mutagens in Chinese hamster cells - Rubashevsky, E.L.; Patskovsky, Y.V.; Kirilenko, S.D.; Varzanova, I.S.; Bogolyubova, O.M.; Lysenko, O.F.; Lukash, L.L. (Биополимеры и клетка, 1996)
In our earlier investigations it was discovered the nuttagenic activity of two recombinant plasmids (pBR322ins and pAins) containing the human preproinsulin gene in cultivated somatic mammalian cells. The preproinsulin gene (allel-1) was able to function under its own promoter in different cell types since it lacked a regulatory element providing tissue-specific expression. Introduction of a frameshift mutation into the region of initiation of the translation of the transgene (allel-2) diminished the mutagenic effect of a corresponding recombinant plasmid on gene level. In this work the mutagenic activity of the recombinant plasmids carrying allel-1 (pBR322ins) andallel-2 (pBR322insN) of the preproinsulin gene was studied using cytogenetic test. It was shown that the presence of allel-2 (that probably had altered expression of the transgene) in the recombinant plasmid structure decreased the level of induced chromosome breaks per cell. It was made a conclusion that not only viruses and their genes but also recombinant DNAs of nonviral origin are able to induce chromosome and gene mutations in mammalian cells. The mutagenic activity of studied recombinant plasmids depends on the level of expression of the transgenes in the cells.